Tetrapod ichnology in Italy: the state of the art Guest editorial - Romano, Marco (2020)
This year, 2020, marks the 150th anniversary of the seminal work by Giulio Curioni (1870), representing the first published scientific contribution on tetrapod footprints from Italy. We took this opportunity to discuss the current state of the art on tetrapod ichnology in our country, with a jubilee volume, titled “Tetrapod ichnology in Italy: the state of the art”. The volume involves the scholars who first pioneered this discipline in Italy in the seventies of the last century, along with all the authors who have worked on the topic in recent decades, and younger generations who have just started to enthusiastically contribute to vertebrate ichnology. After briefly introducing the idea at the base of the Special Volume, as well as some aspects of the discipline and the current methodologies involved in ichnological studies, we present each of the contributions to serve the Italian ichnological heritage.